Analisis Perlindungan Hak Asasi Manusia bagi Pekerja Migran Tidak Berdokumen Tantangan, Kerangka Hukum dan Implikasi Kebijakan - Rahmawati; Immadudin, Muhammad Asad; Bulqis; Jufrin (MAQASID, 2024)
Protection of the basic rights of migrant workers who do not have official documents is a major challenge that urgently needs to be addressed immediately. This article explores the issue of protecting undocumented migrant workers from an often overlooked human rights perspective. Through a normative-empirical research approach, which includes an in-depth legal literature review, this study critically examines the regulations governing migrant workers using a human rights lens. This research identifies a clear link between the lack of protection for undocumented migrant workers and the negative impacts they face, including exploitation, discrimination and abuse. From a human rights perspective, protection of migrant workers should be based on the principles of equality before the law, the right to be protected from discrimination, and recognition of the basic rights of every individual, regardless of their legal status. However, the current legal reality, especially in Indonesia, still prioritizes protection only for migrant workers who have valid documents. This exclusionary approach creates huge disparities, where undocumented migrant workers are denied their basic rights, even though they contribute to the global economy. This article emphasizes the importance of providing basic rights and equal protection to all migrant workers, without discrimination based on their legal status. Although specific regulations regarding the placement of migrant workers can be set to manage the process, requirements and responsibilities of the parties involved, this must not ignore fundamental human rights. Therefore, this article encourages the need for a thorough evaluation of existing laws and regulations, with a focus on legal substance, understanding of stakeholders, as well as fair and consistent implementation regarding protection for migrant workers, without exception. Keywords: human rights, undocumented migrant workers, and legal protection.